UPAYA MENINGKATKAN KEAKTIFAN BELAJAR DAN HASIL BELAJARPENDIDIKAN KEWARGANEGARAAN (PKn) MENGGUNAKAN INDEX CARDMATCH - Eka Meidawati; Trisharsiwi Trisharsiwi (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2015)
Â Abstract:This research aims to enhance the activity of learning and learning outcomescivic educationÂ  (PKn) using active learning strategies in the type of Index Card Match Elementary School VI students Potorono , Bantul . This research was classroom action research was conducted in two cycles . Subjects in the study were students of class VI Semester Elementary School Potorono odd numbering 30 students . The object of this research is the activity of learning and learning outcomes Civics . Data was collected using observation sheets, tests and documentation . The data analysis technique observation sheet is done by calculating the percentage of each indicator , for the achievement test is done by calculating the average grade . The results of the study shows that after application of active learning type of index cards match , active learning and learning outcomes has increased . Judging from the result of an increase in the average percentage of the activity of students in the first cycle of 63.89 % , an increase in cycle II to 80.56 %. The results of studying the average value before action 59.36 , an increase in the first cycle to 67.86 , rising again in the second cycle becomes 75.13 . Thus it can be said that the study of this class action succeeded in increasing the activity of learning and learning outcomes PKn in Elementary School VI students Potorono Bantul , because they have met the success criteria specified .Â